Persepsi Penerima Layanan Jasa Terhadap Kualitas Layanan Pada Instansi Pemerintah - Lilis Endang Wijayanti; Fran Sayekti; Bahagia Tarigan (Bulletin of Management and Business, 2022)
The purpose of this research report is to analyze how service recipients perceive service quality. The object of research is a government agency in the Special Region of Yogyakarta, namely Manpower and Transmigration. The service quality dimensions analyzed include service quality dimensions consisting of physical evidence, reliability, responsiveness, assurance and attention. Primary data used in this research. The data is in the form of responses to questions regarding service quality. Questionnaires are used as a tool to obtain data. Questionnaires were distributed to service users at the Manpower and Transmigration Office. Questionnaires that can be processed 75 questionnaires. The data analysis method used is the average or average opinion of the respondents. The average value of respondents' opinions is a measure of service quality. Service quality is categorized into less good, good and very good. The size is not good if the average value of the variable is in the 1 – 1.67, good size if the average value is in the range of 1.67 to 3.73 while the good category is in the range of 3.74 – 5.00. The results showed that: (1) respondents had a perception that the quality of physical evidence was in the very good category. (2) respondents have a perception that the reliability dimension has good quality, (3) responsiveness according to respondents is of good quality, (4) quality assurance is not good, (5) attention (empathy) and empathy are of good quality.